2019
DOI: 10.1016/j.eurox.2019.100020
|View full text |Cite
|
Sign up to set email alerts
|

Systematic lymphadenectomy for intermediate risk endometrial carcinoma treatment does not improve the oncological outcome

Abstract: Objective To evaluate the indication and performance of systematic lymphadenectomy (SL) in Stage I endometrioid endometrial carcinoma (EEC), at intermediate risk (FIGO IAG2/G3, IBG1/G2) on recurrence, disease-free survival (DFS) and survival. Study design 194 women underwent hysterectomies by laparotomy, with SL (n = 95) or without SL (n = 99) between 1990 and 2014 was evaluated. Diagnosis period, age, BMI, comorbidities, stage, and adjuvant radiotherapy were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…This is in line with other studies, in which a mere 15-20 % of patients had positive lymph nodes after lymphadenectomy [27]. Muallem [11,29]. The latter authors registered no bene t in regard of disease-free or overall survival in patients with intermediate-risk endometrial carcinoma who had undergone a systematic lymphadenectomy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with other studies, in which a mere 15-20 % of patients had positive lymph nodes after lymphadenectomy [27]. Muallem [11,29]. The latter authors registered no bene t in regard of disease-free or overall survival in patients with intermediate-risk endometrial carcinoma who had undergone a systematic lymphadenectomy.…”
Section: Discussionsupporting
confidence: 90%
“…The most common complications of systematic lymphadenectomy are intraoperative bleeding, injury to neighboring organs, postoperative lymph cysts (up to 34.5% of the cases), and lower-limb edema [9,10]. Since more than a half of the patients undergoing a lymphadenectomy (LD) do not have lymph node metastases, the procedure may not improve survival [11][12][13]. The technique of sentinel node biopsy has been re ned over the last few years [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we found that both LVSI status and recurrence rate were largely similar among patients with stage I/II disease regardless of whether surgical lymph node staging was performed. The similarity in recurrence rates suggests that clinical staging is relatively accurate, consistent with the results of 2 large randomized trials involving patients who underwent systematic pelvic lymphadenectomy 23,24. We did find a significant risk for local recurrence for patients with focal LVSI in stage I/II pN0.…”
Section: Discussionsupporting
confidence: 85%
“…Lymphadenectomy in endometrial carcinoma is a controversial aspect of surgical staging, with many prospective studies negating any therapeutic benefits. [ 16 17 ] However, we performed systematic pelvic lymphadenectomy in all cases and coupled it with para-aortic lymphadenectomy in high-risk cases. The median number of pelvic and para-aortic lymph nodes was comparable to studies in existing literature.…”
Section: Discussionmentioning
confidence: 99%